Urine eosinophil‐derived neurotoxin: A potential marker of activity in select eosinophilic disorders. Issue 1 (1st September 2022) - Makiya, Michelle A.; Khoury, Paneez; Kuang, Fei Li; Mata, Alexis Dominique; Mahmood, Sana; Bowman, Abbie; Espinoza, David; Kovacs, Nicholas; Brown, Thomas; Holland, Nicole; Wetzler, Lauren; Ware, JeanAnne M.; et al.
Abstract: Background: Biomarkers of eosinophilic disease activity, especially in the context of novel therapies that reduce blood eosinophil counts, are an unmet need. Absolute eosinophil count (AEC) does not accurately reflect tissue eosinophilia or eosinophil activation. Therefore, the aims of this study were to compare the reliability of plasma and urine eosinophil major basic protein 1, eosinophil cationic protein, eosinophil‐derived neurotoxin (EDN), and eosinophil peroxidase measurement and to evaluate the usefulness of eosinophil granule protein (EGP) measurement for the assessment of disease activity in patients with eosinophil‐associated diseases treated with mepolizumab, benralizumab, or dexpramipexole. Methods: Eosinophil granule protein concentrations were measured in serum, plasma, and urine from healthy volunteers and patients with hypereosinophilic syndrome (HES), eosinophilic granulomatosis with polyangiitis (EGPA), and eosinophilic asthma using a multiplex assay. Results: Urine EGP concentrations remained stable, whereas serum and plasma EGP concentrations increased significantly with delayed processing. Plasma (p) EDN, but not urine (u) EDN, concentration correlated with AEC and negatively correlated with prednisone dose. Both pEDN and uEDN decreased significantly following treatment of HES patients with benralizumab and EGPA patients with mepolizumab. uEDN appeared to increase with clinical relapse in both patient groups. Conclusions: Measurement of EGP in urine is noninvasive and unaffected by cellular lysis. Although plasma and urine EDN concentrations showed a similar pattern following benralizumab and mepolizumab treatment, the lack of correlation between AEC or prednisone dose and uEDN concentrations suggests that measurement of uEDN may provide a potential biomarker of disease activity in patients with HES and EGPA. Abstract : This study compares the reliability and utility of plasma and urine EGP measurements for the assessment of disease activity across a diverse group of EAD and evaluates the usefulness of EGP measurements for the assessment of disease activity in patients with EAD treated with targeted therapeutics.Urine EDN is a stable measure of eosinophilic disease activity that does not correlate with aboslule eosinophil count or prednisone dose. uEDN decreases in response to treatment with mepolizumab and benralizumab but increases prior to AEC and the onset of clinical symptoms in most EAD patients who relapse.Abbreviations: AEC, absolute eosinophil count; EAD, eosinophil‐associated diseases; EDN, eosinophil‐derived neurotoxin; EGP, eosinophil granule proteins; pEDN, plasma EDN; uEDN, urine EDN